Optically tunable catalytic cancer therapy using enzyme-like chiral plasmonic nanoparticles - Kang, Haeun; Yu, Subin; Kim, Ryeong Myeong; Kim, Youngbi; Shin, Sang Chul; Jang, Dohyub; Han, Jeong Hyun; Hong, Sugyeong; Kim, Eunice EunKyeong; Kim, Sun Hee; Ahn, Dong June; Han, Jeong Woo; et al. (Nature Publishing Group, 2025)
Cascade enzymatic reactions in living organisms are fundamental reaction mechanisms in coordinating various complex biochemical processes such as metabolism, signal transduction, and gene regulation. Many studies have attempted to mimic cascade reactions using nanoparticles with enzyme-like activity; however, precisely tuning each reaction within complex networks to enhance the catalytic activity remains challenging. Here, we present enzyme-like chiral plasmonic nanoparticles for optically tunable catalytic cancer therapy. We create chiral plasmonic nanoparticles with glucose oxidase (GOD) and peroxidase (POD) activities, followed by introducing circularly polarized light (CPL). By sequentially activating GOD and POD reactions with right-handed CPL (RC) followed by left-handed CPL (LC), we achieve 1.25- and 1.9-fold enhanced catalytic performance (overall 1.3 times enhancement) compared to non-controlled cascade reactions by creating an optimal acidic environment for the subsequent reaction. Moreover, the D-Au nanoparticle shows a 2-fold higher binding selectivity to D-glucose substrates, attributed to chirality matching. In both cell studies and male mouse models, sequentially irradiated groups (RC followed by LC) exhibit the highest radical generation and the most efficient treatment outcomes compared to the other systems under different irradiation conditions. We believe that our system holds strong potential for medical applications, suggesting a promising platform for catalytic therapy.